The role of motivation in the link between budgetary participation and managerial performance - Abdullah, Shamsul Nahar (Universiti Utara Malaysia, 1998)
This study attempts to replicate and extend the previous study by Brownell and McInnes (1986), who failed to provide evidence of significant influence of motivation on the link between budgetary participation and managerial performance. Using the model developed by House (1971), which was used by Brownell and Mc Innes (1986) to gauge motivation, the present study investigates the influence of each of the components making up the model by using a partial correlation test.